2019
DOI: 10.1111/hex.12883
|View full text |Cite
|
Sign up to set email alerts
|

“About sixty per cent I want to do it”: Health researchers’ attitudes to, and experiences of, patient and public involvement (PPI)—A qualitative interview study

Abstract: Background Funders, policy‐makers and research organizations increasingly expect health researchers in the UK to involve patients and members of the public in research. It has been stated that it makes research “more effective, more credible and often more cost efficient.” However, the evidence base for this assertion is evolving and can be limited. There has been little research into how health researchers feel about involving people, how they go about it, how they manage formal policy rhetoric, and what happ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
175
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(180 citation statements)
references
References 29 publications
5
175
0
Order By: Relevance
“…On a more positive note, having role models and hearing from colleagues experienced in PPI may be bene cial [21]. We hope that the re ections we present in this paper will prompt further attempts by researchers to try novel approaches to engaging patients and the public in their work.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…On a more positive note, having role models and hearing from colleagues experienced in PPI may be bene cial [21]. We hope that the re ections we present in this paper will prompt further attempts by researchers to try novel approaches to engaging patients and the public in their work.…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, researchers may be disinclined to try a novel approach if they feel daunted by the prospect of embedding PPI into their work, especially when resources to undertake this activity in a meaningful manner are lacking [21].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the requirement that certain academic leads attend additional service user meetings and deliver PPI reports to the Executive may have exacerbated unwelcome pressures for staff. When PPI is perceived as an imposition, academics may be less receptive to arguments in its favour [22,42].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a study in the primary care setting found researchers perceived the most positive impact of PPI when the approach included more indicators of good practice such as offering training to contributors (13). However, despite the number of frameworks described, researchers often feel unequipped in knowing how best to involve patients and members of the public and what bene ts they might reasonably expect (18).…”
Section: Introductionmentioning
confidence: 99%